2019
DOI: 10.3390/ani9070468
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Nutritional Status of Yaks (Bos Grunniens) Grazing on the Qinghai-Tibetan Plateau

Abstract: Minerals are essentially important for supporting livestock’s health, as well as productivity. This study aimed to investigate the mineral status of yaks (Bos grunniens) grazing on the Qinghai-Tibetan Plateau (QTP) and the relationship between macro and micro mineral nutrients among soil, forages, and blood in four counties of the QTP. The soil samples (n = 320), forages (n = 320), and blood serum (n = 320) were collected from four randomly selected yak farms in each location during July (warm season) and Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…In addition, the serum concentrations of P in the CONT (1.35 mmol/L) and CaCl group (1.49 mmol/L) were below the recommended level of 1.5 mmol/L [ 28 ]. The serum Ca concentrations of all yaks were in the recommended range (2.25–2.75 mmol/L) [ 26 ], which is consistent with the result of Fan et al (2019) [ 29 ]. These results indicated that the problem of P deficiency in grazing yaks may not only occur in the cold season [ 29 ], but also at the beginning of the warm season.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the serum concentrations of P in the CONT (1.35 mmol/L) and CaCl group (1.49 mmol/L) were below the recommended level of 1.5 mmol/L [ 28 ]. The serum Ca concentrations of all yaks were in the recommended range (2.25–2.75 mmol/L) [ 26 ], which is consistent with the result of Fan et al (2019) [ 29 ]. These results indicated that the problem of P deficiency in grazing yaks may not only occur in the cold season [ 29 ], but also at the beginning of the warm season.…”
Section: Discussionsupporting
confidence: 87%
“…The serum Ca concentrations of all yaks were in the recommended range (2.25–2.75 mmol/L) [ 26 ], which is consistent with the result of Fan et al (2019) [ 29 ]. These results indicated that the problem of P deficiency in grazing yaks may not only occur in the cold season [ 29 ], but also at the beginning of the warm season. Supplementation with MCP had a mitigative effect, whereas CaCl did not.…”
Section: Discussionsupporting
confidence: 87%
“…Under traditional management practices, yaks commonly graze in a full-grazing system with herbage as the only feed [4]. Yaks play an essential function in the alpine ecosystem in various ways, including enhancing plant diversity through creation of microhabitats, providing a livelihood for local herdsmen, enhancing soil structure, and promoting the material circulation and energy flow in the ecosystem [10]. These unique characteristics result in an attractive system explore the adaptation process of yaks to altitudinal gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Yak milk is more nutritive to dairy cow milk in nutrient composition, especially protein and fat [ 4 ], and contains higher fat content of 5.5 to 7.5% as compared to 3.50% in bovine milk and higher protein content of about 4.9–5.9% compared to 3.14% in bovine milk [ 5 ]. Seasonal variation of feeds especially during the cold season greatly influence traditional yak farming [ 6 ]. Supplements are not a common practice even under the low protein content of pastures [ 5 ].…”
Section: Introductionmentioning
confidence: 99%